Capital Mobility in Asia Causes and Consequences - Jongwanich, Juthathip ([S.l.] : ISEAS - Yusof Ishak Institute, 2017)
Asia has benefitted greatly from its integration into the world economy. But globalization has its challenges, including those that are the subject of this excellent new study: how to manage the interface with global capital markets, especially in the current, highly unusual monetary policy settings in the major economies. Dr Juthathip Jongwanich has been researching these issues for several years. In this volume she writes with great authority, providing a comprehensively, succinct and accessible examination of the many complex issues. A must-read volume for policymakers and academics alike.
Capital Mobility in Asia: Causes and Consequences -- Contents -- List of Tables -- List of Figures -- Acknowledgements -- 1. Introduction -- 2. Capital Mobility in Emerging Asian Countries -- 3. Determinants of Inward Foreign Direct Investment in Emerging Asian Countries -- 4. Determinants of Outward Foreign Direct Investment from Emerging Asia -- 5. Determinants of Non-Foreign Direct Investment Capital Flows -- 6. Capital Flows and Real Exchange Rates in Emerging Asian Countries -- 7. Effectiveness of Capital Controls: Evidence from Malaysia and Thailand -- 8. Conclusions and Policy Inferences -- Appendix 1: A Chronology of Capital Account Policy in Malaysia, 1992-2010 -- Appendix 2: A Chronology of Capital Account Policy in Thailand, 1990-2010 -- Bibliography -- Index -- About the Author.
Includes bibliographical references and index.
Keywords: Political economy